KOMUNIKASI DAKWAH WASHATIYAH KH. SANUSI BACO LC - Khaerunnisa, Khaerunnisa (Jurnal Dakwah Tabligh, 2021)
Characteristics of preaching KH. Sanusi Baco Lc is a wasathiyah preacher, moderate. The style of his da'wah is likened to KH. Abdurrahman Ambo Dalle, peace preacher. The tone of the da'wah is cool and touching, contains no criticism unless it is processed in a very subtle language. KH. Abdurrahman Ambo Dalle is the teacher of KH. Sanusi Baco so that the da'wah of the two famous clerics is the same. Peaceful da'wah, greeting and full of advice in the context of amar maruf nahi munkar, avoid conflict. The peaceful da'wah pattern was formed while studying at the DDI Mangkoso Islamic Boarding School which teaches its students to be more tolerant, respectful, and respectful of other groups, even though they have different beliefs. DDI, apart from being an educational institution, is also a da'wah institution. AGH. Sanusi Baco is a role model, not only is his knowledge deep in character, but he is also good at talking, very pleasant to hear. Polite, warm, and harmonious. A true scholar. In the perspective of communication, KH. Sanusi Baco has an optimal da'wah articulation both from his clothes and his ability to choose diction and compose more narrative words. Have respect for humanity. Humanizing humans is an important dimension in the context of communication, namely giving high appreciation to the people. <pre id="tw-target-text" class="tw-data-text tw-text-large XcVN5d tw-ta" style="font-family: inherit; unicode-bidi: isolate; font-size: 28px; line-height: 36px; background-color: #f8f9fa; border: none; padding: 2px 0.14em 2px 0px; position: relative; margin: -2px 0px; resize: none; overflow: hidden; width: 270px; white-space: pre-wrap; overflow-wrap: break-word; color: #202124;" dir="ltr" data-placeholder="Translation">Characteristics of preaching KH. Sanusi Baco Lc is a wasathiyah preacher, moderate. The style of his da'wah is likened to KH. Abdurrahman Ambo Dalle, peace preacher. The tone of the da'wah is cool and touching, contains no criticism unless it is processed in a very subtle language. KH. Abdurrahman Ambo Dalle is the teacher of KH. Sanusi Baco so that the da'wah of the two famous clerics is the same. Peaceful da'wah, greeting and full of advice in the context of amar maruf nahi munkar, avoids conflict. The peaceful da'wah pattern was formed while studying at the DDI Mangkoso Islamic Boarding School which teaches its students to be more tolerant, respectful and respectful of other groups, even though they have different beliefs. DDI, apart from being an educational institution, is also a da'wah institution. AGH. Sanusi Baco is a role model, not only is his knowledge deep in character, he is also good at talking, very pleasant to hear. Polite, warm and harmonious. A true scholar. In the perspective of communication, KH. Sanusi Baco has an optimal da'wah articulation both from his clothes and his ability to choose diction and compose more narrative words. Have respect for humanity. Humanizing humans is an important dimension in the context of communication, namely giving high appreciation to the people. His da'wah communication reflects moderation, more amar maruf so that it is always cool. Very rarely talk about nahi munkar. This is what distinguishes some of the speakers who are dominant in speaking nahi munkar, always blaming. The message of his da'wah is full of advice and puts forward the commandments so that people are taught how to behave properly. People don't always ask for nahi munkar. That is why his da'wah is always accepted because he always puts forward amar maruf, accepted outside other religions of Islam. AGH. Sanusi Baco is a figure of a Christian who obeys iltizam according to his intentions when confronted with God. There are only two activities in his life, education and da'wah. Provide advice and educate. Ulama who are very diligent in studying Islamic sciences. Never heard of unscientific lectures, if the congress always shows references. His ability to communicate reflects the depth of his knowledge, his lectures are accepted by all groups because they are good at speaking and the material is more moderate, washathiyah.